Strengthening Inclusive Education: Unraveling Prerequisites for Children with Intellectual Disabilities - Niure, Dhruba Prasad; Shrestha, Madhav Kumar (Interdisciplinary Research in Education, 2023)
This article highlights the prerequisites that need to be considered to provide inclusive education to children with intellectual disabilities. Educating these children in inclusive settings not only ensures quality instructional services but also prepares them for adult life in the future. Nevertheless, a number of factors, such as government policies, resource availability, teacher attitudes, community support, and the quality of accessible learning materials, have a tremendous impact on ensuring their inclusion in education. Neglecting the better education of these children may lead to societal burdens, and inclusive education can help students coexist more effectively in broader social contexts as adults. Since students with intellectual disabilities often face challenges in processing and expressing information due to their unique learning characteristics, they must be treated differently using evidence-based practices. Accommodations and modifications in the curriculum, pedagogy, and assessment should be made based on their learning profiles. Teachers should have high expectations and provide quality support for all students to ensure their access to the general curriculum. Educational services for children with intellectual disabilities in Nepal reveal a significant policy-practice gap. Though there are policy provisions for providing inclusive education to all children, children with intellectual disabilities are often segregated, leading to inadequate support and poor education quality. This situation deprives them of their right to study alongside typically developing peers.